Augmenting Leucaena leucocephala biomass with mineral fertiliser on rainwater use efficiency, agronomic efficiency and yields on sorghum (Sorghum bicolor [(L.) Moench]) under rainwater harvesting techniques in semi-arid region of Zimbabwe. Issue 7 (July 2022) - Kugedera, Andrew Tapiwa; Nyamadzawo, George; Mandumbu, Ronald
Abstract: Food security in semi-arid regions is threatened by declining soil fertility, soil moisture stress and long frequent droughts as a result of erratic rainfall. Therefore we assessed the effects of augmenting Leucaena leucocephala biomass (organic manure) with mineral fertiliser on rainwater use efficiency, agronomic efficiency, grain and stover yields for two sorghum varieties (Macia and SV1) under rainwater harvesting techniques. The experiment was laid in split-split plot arrangement with rainwater harvesting method as main plot factor, with Leucaena biomass + NPK fertiliser as subplot factor and sorghum variety as sub-sub plot factor over three cropping seasons. Data collected include rainwater use efficiency, agronomic efficiency, grain and stover yields. Results show that tied contours have significantly (p ≤ 0.05) higher grain and stover yields from all varieties and seasons. Irregardless of sorghum variety, tied contours had significant (p ≤ 0.05) sorghum grain and stover yield followed by infiltration pits and lastly standard contours. Grain and stover yields improved with increasing levels of Leucaena biomass + NPK fertiliser combination. Highest grain yields observed were 1.146 t ha −1 (Macia) and 1.1 t ha −1 (SV1) from tied contour +15 t ha −1 biomass +150 kg ha −1 NPK fertiliser treatments. Rainwater use efficiency was significantly (p ≤ 0.05) higher from tied contours compared to infiltration pits and standard contour. Rainwater use efficiency was statistically (p ≤ 0.05) influenced by increasing application levels of Leucaena biomass + NPK fertiliser in all seasons. Agronomic efficiencies were considerably (p ≤ 0.05) affected by rainwater harvesting, Leucaena biomass + NPK fertiliser and interaction of all factors. It can therefore be concluded that Leucaena biomass + NPK fertiliser, tied contours and infiltration pits improve sorghum yields. Augmenting 2.5 t ha −1 biomass with 25 kg ha −1 NPK fertiliser under tied contours and Macia have better agronomic efficiency. Abstract : Rainwater harvesting; L. leucocephala ; NPK fertiliser; Sorghum ; Semi-arid regions; Sandy soils.